Physicochemical, antioxidant, and antimicrobial study in Nepalese honey - Adhikari, Amrita; Thapa, Nabin Kumar; Gurung, Anita; Parajuli, Niranjan (BIBECHANA, 2025)
Five honey samples, mostly from western Nepal, were analyzed for physicochemical properties, TPC, TFC, antioxidant, and antimicrobial assays. The results were found to be within the acceptable range, while some samples had higher moisture, HMF, and total ash levels. The TPC was in the range of 8.420 to 9.920 mg GAE and the TFC was between 0.039 to 0.103 mg QE. The IC50 values were calculated of which Forest honey was found to have the lowest IC50 value i.e. 7.735 ± 0.008 mg/mL. Additionally, samples also showed a large zone of inhibition against four pathogens. Besides, the correlation between physicochemical parameters, TFC, TPC, and antioxidant activity was established by using Pearson’s correlation and PCA. It displayed that the variables IC50 , reducing sugar, HMF, and TFC in samples were positively correlated with one another and inversely with total ash (%), acidity as formic acid (%), andmoisture (%).